Free‐breathing liver fat quantification using a multiecho 3D stack‐of‐radial technique - Armstrong, Tess; Dregely, Isabel; Stemmer, Alto; Han, Fei; Natsuaki, Yutaka; Sung, Kyunghyun; Wu, Holden H. (Magnetic resonance in medicine, 2018)
Purpose The diagnostic gold standard for nonalcoholic fatty liver disease is an invasive biopsy. Noninvasive Cartesian MRI fat quantification remains limited to a breath‐hold (BH). In this work, a novel free‐breathing 3D stack‐of‐radial (FB radial) liver fat quantification technique is developed and evaluated in a preliminary study. Methods Phantoms and healthy subjects (n = 11) were imaged at 3 Tesla. The proton‐density fat fraction (PDFF) determined using FB radial (with and without scan acceleration) was compared to BH single‐voxel MR spectroscopy (SVS) and BH 3D Cartesian MRI using linear regression (correlation coefficient ρ and concordance coefficient ρc) and Bland‐Altman analysis. Results In phantoms, PDFF showed significant correlation (ρ > 0.998, ρc > 0.995) and absolute mean differences < 2.2% between FB radial and BH SVS, as well as significant correlation (ρ > 0.999, ρc > 0.998) and absolute mean differences < 0.6% between FB radial and BH Cartesian. In the liver and abdomen, PDFF showed significant correlation (ρ > 0.986, ρc > 0.985) and absolute mean differences < 1% between FB radial and BH SVS, as well as significant correlation (ρ > 0.996, ρc > 0.995) and absolute mean differences < 0.9% between FB radial and BH Cartesian. Conclusion Accurate 3D liver fat quantification can be performed in 1 to 2 min using a novel FB radial technique. Magn Reson Med 79:370–382, 2018. © 2017 International Society for Magnetic Resonance in Medicine.